Long-time visual functional results of cataract surgery on low vision patients - Eva I Mönestam (Dove Medical Press, 2008)
Eva I Mönestam, Britta M Lundqvist, Åsa C JonssonDepartment of Clinical Sciences/Ophthalmology, Umeå University, Umeå, SwedenBackground/aims: To assess longitudinal 5-year results of cataract surgery on low vision patients.Methods: In this prospective, long-time, observational case-series, we report the outcome regarding the subjective visual function (n = 35) assessed by a visual function questionnaire (VF-14) and the visual acuity (n = 30) of surviving low vision patients 5 years after surgery. We compare with data recorded on the same patients before surgery and 4 months postoperatively.Results: Five years after surgery, 57% had unchanged or better VF-14 score compared with preoperatively, and 37% compared with postoperatively. Maculopathy patients had a significantly larger deterioration 5 years after surgery compared with postoperatively (40.2 versus 51.7, p = 0.004), but for the glaucoma patients there was no significant change (52.6 versus 53.1). There were no significant associations between age of the patient and change in VF-14 score or change in visual acuity 5 years after surgery, neither compared with before surgery nor postoperatively.Conclusion: Results suggest a favorable functional outcome 5 years after cataract surgery on most low-vision patients. Glaucoma patients have a more stable outcome than patients with macular degeneration. The severity of the disease-process for each individual patient might be the most important factor affecting the long-time results.Keywords: low vision, cataract surgery outcome, long-time results